Pengaruh ROA, ROE, dan EPS terhadap Harga Saham Bank Umum Kelompok BUKU 4 - Yasmin Aulia Tahir; Tjetjep Djuwarsa; Ine Mayasari (Indonesian Journal of Economics and Management, 2021)
This research aims to determine the effects of ROA, ROE, and EPS on stock prices of commercial banking category of BUKU 4 for the 2014-2019 periods. The populations in this study is the conventional commercials bank group BUKU 4. The sampling technique selected was through the samples jenuh method which made the entire population into the samples and obtained as many as 7 companies for 6 years starting from 2014-2019. The data in this research is secondary data. The data analysis method used is a quantitative approach with the panel data method. The analytical tool used in this study is the Eviews 9 software. The result of the studies explained that the Return on Assets (ROA) does not have a partially significant effect on stock prices. Meanwhile, Return on Equity (ROE) and Earning Per Share (EPS) has a partially significant effect on stock prices. In addition, Return on Assets (ROA), Return on Equity (ROE), and Earning Per Share (EPS) simultaneously have a significants effect on stock prices.